2021
DOI: 10.1097/md.0000000000026357
|View full text |Cite
|
Sign up to set email alerts
|

The effects of core stability training in nurses with nonspecific low back pain

Abstract: To investigate the effect of core stability training on nonspecific low back pain (NSLBP) in nurses. The data were collected retrospectively by reviewing the patient's medical records and pain questionnaires in our rehabilitation center. A total of 40 nurses with NSLBP were included and divided into observation group and control group. Each group were given routine health education for NSLBP. Core stability training was performed in observation group for 4 weeks. Surface electromyography (sEMG) eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Ferreira et al also found that exercise therapy and an educational booklet were equivalent in terms of outcome benefits [ 15 ]. Quality of life was not one of the outcome measures in their studies [ 15 , 17 ], but it was greatly improved by core stability exercise therapy in our study. Participants with low back pain benefited more from group-based exercise than home-based exercise in terms of personal well-being, work satisfaction, desire to exercise, and energy in engagement with family and friends [ 33 ].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Ferreira et al also found that exercise therapy and an educational booklet were equivalent in terms of outcome benefits [ 15 ]. Quality of life was not one of the outcome measures in their studies [ 15 , 17 ], but it was greatly improved by core stability exercise therapy in our study. Participants with low back pain benefited more from group-based exercise than home-based exercise in terms of personal well-being, work satisfaction, desire to exercise, and energy in engagement with family and friends [ 33 ].…”
Section: Discussionmentioning
confidence: 54%
“…The studies by Zou et al (2021) and Ferreira et al (2021) were designed to evaluate the add-on effect of exercise therapy combined with health consultation. Zou et al showed that core stability exercise and health education together provided more effects on pain reduction and functional improvement than health education alone [ 17 ]. Ferreira et al also found that exercise therapy and an educational booklet were equivalent in terms of outcome benefits [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, motor control exercises affecting local muscles (lumbar and lateral abdominal muscles) have been seen to improve postural stability and/or reduce back problems in young adults [11]. Core stability training has been reported to be an effective intervention for balance performance [12][13][14]. Szafraniec et al [12] reported that 4 weeks of core stability training improved balanced performance in health adults.…”
Section: Introductionmentioning
confidence: 99%
“…Szafraniec et al [12] reported that 4 weeks of core stability training improved balanced performance in health adults. Zou et al [13] reported that 4 weeks core stability training improved balance ability in young adults with LBP. A meta-analysis conducted by Wang et al [14] indicated that core stability training can improve the trunk function balance and mobility of the patients with young LBP patients.…”
Section: Introductionmentioning
confidence: 99%